Designing and implementing foundation courses for allied health science students employing Kern’s six steps: a narration of perspective - Neeti Bhat; Aashma Dahal; Satish Kumar Deo; Jayendra Bajracharya (Cogent Education)
This narrative paper describes the process of designing foundation courses for undergraduate programs in ‘allied health sciences’, at Madan Bhandari Academy of Health Sciences, Nepal. The primary objective of the courses was to provide a smooth transition for undergraduate students into their new academic, social, and professional responsibilities. Thirteen brief modules of foundational courses were designed on three social and cognitive domains: task mastery, acculturation and role clarification. We employed Kern’s six-step model, which is a widely accepted, evidence-based, and learner-centric systematic framework for curriculum designWhile implementing the courses, we, faced a multitude of challenges like budget shortages, training of human resources, low student readiness, and infrastructural limitations. This paper is an account of our experiences during the process . Through this perspective paper, we aim to highlight the importance of foundational courses in undergraduate programs and also draw the attention of policy-makers to the need of innovational strategies for easy transitioning and adjustmentof students from higher secondary to undergraduate level. We conclude that a smooth transition could offer better chances for the students to succeedin their academic programs too, and thus, save both personal and organizational resourcesotherwise spent in managing academic failures.